Answer:
The first three terms of the given sequence are:
[tex]f(1)=9,f(2)=6\ and\ f(3)=3[/tex]
Step-by-step explanation:
Given:
A recursive function is given as:
[tex]f(n)=(f(n-1)-3[/tex]
The first term is [tex]f(1)=9[/tex]
We need to find the remaining two terms [tex]f(2)\ and\ f(3)[/tex]
In order to find [tex]f(2)\ and\ f(3)[/tex], we put [tex]n=2[/tex] and [tex]n=3[/tex] and simplify the recursive function.
For [tex]n=2[/tex], the recursive function is given as:
[tex]f(2)=f(2-1)-3\\f(2)=f(1)-3\\f(2)=9-3=6........[\because f(1)=9][/tex]
Therefore, the second term is [tex]f(2)=6[/tex]
For [tex]n=3[/tex], the recursive function is given as:
[tex]f(3)=f(3-1)-3\\f(3)=f(2)-3\\f(2)=6-3=3........[\because f(2)=6][/tex]
Therefore, the third term is [tex]f(3)=3[/tex]
Hence, the first three terms of the given sequence are:
[tex]f(1)=9,f(2)=6\ and\ f(3)=3[/tex]